EFFECT OF EMPLOYER BRANDING AND PRESTIGE ON INTENTION TO APPLY IN THE TOP 5 E-COMMERCE IN INDONESIA - Susilo, Sophia Reni (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2022)
Employer branding is the image and reputation of the organization as an ideal place to work. The purpose of this study was to determine the effect of the employer's brand strategy on the intention to apply for jobs in the top five e-commerce in Indonesia. This research was conducted on students at seven universities in Jakarta representing the second-level regions of DKI Jaya. The sampling method used probability sampling with cluster sampling. Data was collected by distributing questionnaires. This type of research is quantitative and uses the SmartPLS 3.0 program. The results showed that publicity had a significant effect on the work environment, task attractiveness, and pay attractiveness, publicity had no significant effect on career opportunities, WOM had a significant effect on the work environment, task attractiveness, and pay attractiveness, advertising had a significant effect on the work environment. and career opportunities, advertisements have no significant effect on task attractiveness and pay attractiveness, work environment, pay attractiveness, career opportunities, and prestige have a significant effect on intentions to apply for work, while task attractiveness does not significantly affect intentions to apply for work. Overall, the employer's brand strategy and prestige influence job application intentions.